Efficiency of a formulated condiment (duqqa) in mitigation of diabetes and its complications induced by streptozotocin-nicotinamide in rats - Rasha S. Mohamed; Ahmed M. Abdel-Salam (Shahrekord University of Medical Sciences, 2021)
Introduction: Duqqa is a condiment, consisting of black pepper, cumin, sesame, coriander and high amount of salt. Reducing salt and adding other beneficial items to traditional duqqa can make it suitable dietary supplement for diabetes management. The current study aimed to assess the effect of a modified duqqa on diabetes and its complications in diabetic rats. Methods: The modified duqqa was formulated by mixing grounded fermented wheat, sesame, coriander, cumin, chicory leaves, cinnamon, turmeric and date seeds powder and studied in diabetic rats which were developed by streptozotocin-nicotinamide injection. Thirty-two rats were divided into four groups (n = 8) including non-diabetic, diabetic control and the other two groups fed on balanced diet supplemented with either 10 or 20% of duqqa prior the induction of diabetes (for one week) to the end of the experiment (8 weeks). Results: The dietary supplementation with 10 and 20% of the formulated duqqa prior the induction of diabetes did not delay the onset of diabetes in rats but produced reduction (32.56% and 50.47%, respectively) in the glucose levels of diabetic rats. Also, diabetic rats fed on the formulated duqqa showed insulin concentrations higher than that of diabetic control rats. Feeding diabetic rats on the formulated duqqa reversed the elevation of kidney lipid peroxidation and nitric oxide, limited the disturbance in the lipid profile as well as liver and kidney functions and elevated both serum and femur magnesium concentrations. Conclusion: The results indicated the hypoglycemic effect of the formulated duqqa and its efficiency in delaying diabetes complications.